MPT64 gene mutations leading to non-reactivity on a rapid immunochromatographic assay - Chew, Ka Lip; Lin, Raymond Tzer Pin; Teo, Jeanette Woon Pei (The Journal of Infection in Developing Countries, 2017)
This item has no abstract. Follow the links on the page to access the full text.